SIMILARITIES AND DIFFERENCES OF DEGREE OF ADJECTIVE IN ENGLISH AND RUSSIAN LANGUAGES - Odilova Mashkhura; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
Annotation: Adjectives are words that modify or describe nouns or pronouns by providing additional information about their qualities, characteristics, or attributes. They serve to enhance the specificity and vividness of language by adding detail to nouns and pronouns. Adjectives possess several distinctive features, including degrees of comparison and varied syntactic functions. This article aims to explore the perspectives of both English and Russian scholars on this linguistic phenomenon. By delving into relevant theories and drawing upon examples from English and Russian literature, we are about to compare and contrast the terminologies and approaches employed in each language.